2016
DOI: 10.1101/060830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneity of cognitive decline in dementia: a failed attempt to take into account variable time-zero severity

Abstract: NOTE: The biases seen in simulations of Temporal Clustering appear to be even worse in real applications. While this was a novel and interesting approach, ultimately this work has been discontinued. I feel the biases are due to propagated error in estimating individual level offsets based on a single noisy measure, amplified by the fact that high MMSE scores change very slowly and therefore many estimates are from near an asymptote on the left hand of the model. We continue to work in this area, with other app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The trend identified in Fig 12 is an excellent match with data from well-conducted longitudinal studies 22,25,26, . Figure 14.…”
Section: Observable Cognitive Capacitysupporting
confidence: 74%
“…The trend identified in Fig 12 is an excellent match with data from well-conducted longitudinal studies 22,25,26, . Figure 14.…”
Section: Observable Cognitive Capacitysupporting
confidence: 74%
“…The derived chronicity for each participant is then used as a covariate in further models. Kiddle et al ( Kiddle et al, 2017 ) point out a potential flaw of trajectory approaches when used with short follow-up, which is that the realized curves may be too sensitive to participants’ initial measurement, leading to unrealistic “always has been high” or “always will be low” trajectories; particularly if subjects are first recruited across a wide range of severity. Indeed, using our data an attempt to fit a trajectory model displayed exactly the artifacts they point out.…”
Section: Discussionmentioning
confidence: 99%
“…Code sharing can be facilitated by websites such as GitHub (https://github.com/), which allow both private and public sharing of code, as well as version control. Care must of course be taken not to release data that is sensitive, including within the script itself, but we have shown that this can be achieved [59].…”
Section: Challenges and Recommendationsmentioning
confidence: 99%